2016
DOI: 10.5194/se-7-1591-2016
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of crustal density heterogeneities on regional seismic wave propagation

Abstract: Abstract. Density heterogeneities are the source of mass transport in the Earth. However, the 3-D density structure remains poorly constrained because travel times of seismic waves are only weakly sensitive to density. Inspired by recent developments in seismic waveform tomography, we investigate whether the visibility of 3-D density heterogeneities may be improved by inverting not only travel times of specific seismic phases but complete seismograms.As a first step in this direction, we perform numerical expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 95 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…In previous experiments, we showed that density has a clear imprint on the seismic wavefield and can in principle be inverted for (Płonka et al, 2016;Blom et al, 2017). This is especially the case at longer periods (Takeuchi and Saito, 1972).…”
Section: Spike Testsmentioning
confidence: 67%
“…In previous experiments, we showed that density has a clear imprint on the seismic wavefield and can in principle be inverted for (Płonka et al, 2016;Blom et al, 2017). This is especially the case at longer periods (Takeuchi and Saito, 1972).…”
Section: Spike Testsmentioning
confidence: 67%
“…It is imaged in various other studies (e.g. Amaru, 2007;Biryol et al, 2011;Portner et al, 2018) and is interpreted as the deeper part of the Cyprian slab. In previous studies, the shallow part of this slab was imaged as near horizontal, stretching northward from the Cyprus trench (e.g.…”
Section: High-velocity Structuresmentioning
confidence: 78%
“…ParaView (Ahrens et al, 2005). Amaru, 2007;Biryol et al, 2011;Portner et al, 2018;Hosseini, 2016). In our model, the fast anomaly flattens out towards the 410 km discontinuity and is not imaged in deeper parts (Fig.…”
Section: High-velocity Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the parameterization specifies six parameters at each point not all can be resolved independently. In order to reduce the possible bias from a fixed density (Blom et al., 2017; Płonka et al., 2016), we update the density through the iterations but abstain from the interpretations due to the inferior resolution relative to the seismic velocity parameters. The number and type of velocity parameters being inverted for are varied through the stages of the multi‐scale inversion (see Section 3.3).…”
Section: Methodsmentioning
confidence: 99%